Exploring South Africa’s Policy Dilemmas and Strategic Pathways - Baneng Naape (Rescollacom (Research Collaborations Community), 2026)
This study had two primary objectives. It aimed to present sterilised facts on South Africa’s recent economic performance and its underlying drivers, and to propose actionable policy measures for addressing related socioeconomic challenges. The study reveals that while the democratic government has made strides in addressing historical disparities, significant gaps persist, particularly in tackling income and wealth inequality, enhancing state legitimacy, and promoting equitable economic opportunities and outcomes for all. The country continues to grapple with deep-rooted issues, including disparities in education, deteriorating infrastructure, widespread unemployment and inequality, and systemic corruption. The government should prioritise educational equity by investing in under-resourced schools, attracting skilled educators, and fostering inclusive learning environments. There is also a pressing need to strengthen infrastructure management, prioritise ongoing maintenance, and channel resources into research and development to spur innovation. To address inequality, the government should implement supply-side solutions, focusing on skill development, supporting small businesses, and enforcing fair labour practices. Combating corruption requires principled leadership, transparent governance, and active citizen engagement. Implementing these measures could help ease structural constraints and deliver both medium and long-term socioeconomic gains.